MicroRNA‐497 inhibition mitigates myocardial infarction via enhancing wingless/integrated signal pathway in bone marrow mesenchymal stem cells. Issue 8 (30th March 2019) - Tang, Yu; Zhong, Zhiying; Wang, Xiaohua; Wang, Yunxia; Liu, Yanfeng; Chang, Zhitang
Abstract: Objective: High association between microRNA‐497 (miR‐497) inhibition and the improvement of myocardial infarction (MI) has been proved. Bone marrow mesenchymal stem cells (BMSCs) therapy is regarded as a highly promising approach to MI treatment. We studied the functional role of miR‐497 inhibition in the transplantation of BMSCs for MI treatment. Methods: BMSCs were isolated from 10 to 14 days old male Sprague‐Dawley (SD) rats for in vitro and in vivo experiments. First, flow cytometry was used for BMSCs identification. miR‐497 antagomir and agomir were transfected into BMSCs, and the migratory capacity was detected by wound healing assay. Protein levels were analyzed by Western blot analysis. Second, rat MI models were constructed and injected with each experimental group BMSCs. Four weeks later, the cellular morphology of cardiomyocyte and infarcted size was observed after histopathologic evaluation (HE) and Masson's trichrome staining. Moreover, WNT3A siRNA (siWNT3A) was used for further investigating the involvement of Wnt/β‐catenin pathway. Results: BMSCs were confirmed to be CD90+ CD45− CD11b/c− cells. The number of rats with wound closure increased more in miR‐497 inhibitor group than that in agomir group, the number markedly decreased in agomir group ( P  < 0.01). As the miR‐497 decreased, the protein levels of WNT3A, matrix metalloproteinase‐9 and β‐catenin were notably increased. The injection of BMSCs inhibiting miR‐497 repaired almost all infarcted zones. siWNT3A, on the contrary, could decrease the wound closure rate and relative protein levels and inhibit MI treatment. Conclusion: miR‐497 antagomir contributes to BMSCs transplantation for MI treatment by Wnt/β‐catenin activation, and Wnt/β‐catenin pathway is essential for the functional effects of miR‐497 antagomir. Abstract : After injection of microRNA‐497 (miR‐497) inhibited Bone marrow mesenchymal stem cells (BMSCs), the myocardial infarct area basically disappeared in the myocardial infarction (MI) rat heart. The cotransfection of WNT3A siRNA (siWNT3A) reversed the treatment effects of miR‐497 inhibited BMSCs on the MI, indicating the treatment effect of miR‐497 inhibition on BMSCs therapy was attributed to the involvement of Wnt signal pathway.